The Proteome of Equine Oviductal Fluid Varies Before and After Ovulation: A Comparative Study - Fernández-Hernández, Pablo; Marinaro, Federica; Sánchez-Calabuig, María Jesús; García-Marín, Luis Jesús; Bragado, María Julia; González-Fernández, Lauro; Macías-García, Beatriz (Frontiers in Veterinary Science, 2021)
Equine fertilization cannot be performed in the laboratory as equine spermatozoa do not cross the oocyte´s zona pellucida in vitro. Hence, a more profound study of equine oviductal fluid (OF) composition at the pre-ovulatory and post-ovulatory stages could help to understand what components are required to achieve fertilization in horses. Our work aimed to elucidate the proteomic composition of equine OF at both stages. To do this, OF was obtained postmortem from oviducts of slaughtered mares ipsilateral to a pre-ovulatory follicle (n = 4) or a recent ovulation (n = 4); the samples were kept at -80 °C until analysis. After protein extraction and isobaric tags for relative and absolute quantification (iTRAQ) labelling, the samples were analyzed by nanoliquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). The analysis of the spectra resulted in the identification of a total of 1173 proteins present in pre-ovulatory and post-ovulatory samples; among these, 691 were unique for Equus caballus. Proteins from post-ovulatory oviductal fluid were compared with proteins from pre-ovulatory oviductal fluid and were categorized as up- (positive log fold change) or down-regulated (negative log fold change); 15 proteins were found to be down-regulated in the post-ovulatory fluid and 156 were up-regulated in the post-ovulatory OF compared to the pre-ovulatory fluid; among the upregulated, 87 were included in the pathway metabolism of proteins. The identified proteins were related to sperm-oviduct interaction, fertilization, and metabolism, among others. Our data reveal consistent differences in the proteome of equine OF prior and after ovulation, helping to increase our understanding in the factors that promote fertilization and early embryo development in horses.